Antidepressants as emerging contaminants: Occurrence in wastewater treatment plants and surface waters in Hangzhou, China - Chen, Yuan; Wang, Junlin; Xu, Peiwei; Xiang, Jie; Xu, Dandan; Cheng, Ping; Wang, Xiaofeng; Wu, Lizhi; Zhang, Nianhua; Chen, Zhijian (Frontiers in Public Health, 2022)
Aims Antidepressants have aroused wide public concern due to their widespread presence in water and their harm to human health and environment. This study was designed to evaluate the contribution of wastewater treatment plants (WWTPs) to the presence of antidepressants in the surface water. Methods Data was evaluated by analyzing water samples collected from the influent, effluent, upstream and downstream of the WWTPs on the rivers of interest in Hangzhou, Zhejiang Province, China. Besides, the study also assessed the impact of the release of antidepressants from WWTPs to the surface water on the drinking water. An automatic solid-phase extraction combined with ultra-high performance liquid chromatography-tandem triple quadrupole mass spectrometry (UPLC-MS/MS) was used to detect antidepressants. Results The most abundant compound was venlafaxine, followed by citalopram, sertraline, and fluvoxamine with concentrations between 0.6 and 87 ng/L. Antidepressants showed maximum concentrations at the effluent outlets of the WWTPs, and greater concentrations were found downstream than upstream of the WWTPs in Qiantang River. The results of source water and finished water showed that the detection concentration was lower than the detection limit of the method. Conclusions The less impact of the release of antidepressants from WWTPs to the surface water on the drinking water was identified. Nevertheless, these compounds were hardly removed by wastewater treatment processes. Thus, their risks deserve close attention.